Identifikasi mineral kalsit di kawasan sungai desa Sumbermiri kecamatan Lengkong kabupaten Nganjuk dengan metode geomagnet - Prita Putri Dianti; Sutrisno Sutrisno; Burhan Indriawan (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
This research aims to identify the mineral rocks that are found in the river village districts of Sumbermiri village, Lengkong district, Nganjuk regency. XRF tests have been conducted on a rock an the result was 57 percent of the rocks is a calcite minerals. He method used is the geomagnetics, is by measurig the value of the total magnetic field in the area of research using the magnetometer. Data collection is done three times at each point, then retrieved the data with the smallest noise value to be processed. Corection calculation of the daily (diurnal) and IGRF corection. IGRF value of research location is 33281,4, with the degree of inclination is 25,9993 and declination 8,1201. Then the data has be performed using a contour in the Surfer 10 and Magpick transform and see the contours of the surface magnetics field. Interpretation of results indicates calcite mineral content in the study area. Mag2DC modeling obtained using 2D contour transversely. On the first line, calcite rock has been indentified susceptibility of -2,955 - -0,651 with the misfit 747,79. Second line has been susceptibility of -0,897 - -0,249 with the misfit 592,35. Third line has been susceptibility of -0,509 - -0,005 with the misfit 867,85.